Long-Term Outcome for Early Stage Thymoma: Comparison between Thoracoscopic and Open Approaches - Maniscalco, Pio; Tamburini, Nicola; Quarantotto, Francesco; Grossi, William; Garelli, Elena; Cavallesco, Giorgio (The Thoracic and Cardiovascular Surgeon, 2015)
Background Complete surgical excision is the most important long-term prognostic factor of thymomas. Although video-assisted thoracoscopic surgery (VATS) has been reported as an effective treatment to excise mediastinal thymic lesions, it has not replaced median sternotomy as the standard approach because of the lack of long-term follow-up studies. The objective of this study was to analyze and to compare the outcome of VATS extended thymectomy with the traditional open approach.Methods This is a single center's retrospective study of 27 patients submitted to surgery for early stage thymomas between 1995 and 2007. Histologic subtype and clinicopathologic staging were classified, respectively, according to World Health Organization and Masaoka criteria. Patients with preoperative computed tomography scan evidence of clinical Masaoka stage 1 thymomas were selected for VATS thymectomy with unilateral technique.Results All patients successfully underwent surgery: 3 with VATS and 4 with an open approach. There were no differences in time of surgery and postoperative complication between the two groups. Patients who had VATS had shorter postoperative hospital stay than patients who had open technique. After a median follow-up of 123 months, there were no postoperative recurrences.Conclusion VATS is a safe operation and has comparable effectiveness to the open technique in terms of oncological radicality for small, early stage thymoma.
Keywords: thymus; thymoma; thoracoscopy; VATS; minimally invasive surgery